Brain ageing in schizophrenia: evidence from 26 international cohorts via the ENIGMA Schizophrenia consortium - Constantinides, Constantinos; Han, Laura K M; Alloza, Clara; Antonucci, Linda Antonella; Arango, Celso; Ayesa-Arriola, Rosa; Banaj, Nerisa; Bertolino, Alessandro; Borgwardt, Stefan; Bruggemann, Jason; Bustillo, Juan; Bykhovski, Oleg; et al. (Molecular psychiatry, 2023)
Schizophrenia (SZ) is associated with an increased risk of life-long cognitive impairments, age-related chronic disease, and premature mortality. We investigated evidence for advanced brain ageing in adult SZ patients, and whether this was associated with clinical characteristics in a prospective meta-analytic study conducted by the ENIGMA Schizophrenia Working Group. The study included data from 26 cohorts worldwide, with a total of 2803 SZ patients (mean age 34.2 years; range 18-72 years; 67% male) and 2598 healthy controls (mean age 33.8 years, range 18-73 years, 55% male). Brain-predicted age was individually estimated using a model trained on independent data based on 68 measures of cortical thickness and surface area, 7 subcortical volumes, lateral ventricular volumes and total intracranial volume, all derived from T1-weighted brain magnetic resonance imaging (MRI) scans. Deviations from a healthy brain ageing trajectory were assessed by the difference between brain-predicted age and chronological age (brain-predicted age difference [brain-PAD]). On average, SZ patients showed a higher brain-PAD of +3.55 years (95% CI: 2.91, 4.19; I2 = 57.53%) compared to controls, after adjusting for age, sex and site (Cohen's d = 0.48). Among SZ patients, brain-PAD was not associated with specific clinical characteristics (age of onset, duration of illness, symptom severity, or antipsychotic use and dose). This large-scale collaborative study suggests advanced structural brain ageing in SZ. Longitudinal studies of SZ and a range of mental and somatic health outcomes will help to further evaluate the clinical implications of increased brain-PAD and its ability to be influenced by interventions.
Keywords: Young Adult; Male; Aging; magnetická rezonanční tomografie; mladý dospělý; Adolescent; Brain; Schizophrenia; Adult; Aged; dospělí; Prospective Studies; mužské pohlaví; senioři; mladiství; lidé; ženské pohlaví; Humans; schizofrenie; stárnutí; mozek; Magnetic Resonance Imaging; Female; lidé středního věku; Middle Aged; prospektivní studie